The Influence of Information Technology-Based Career Competencies and Management on the Work Effectiveness of Lecturers at Gorontalo State University - Santi Rauf; Udin Hamim; Juriko Abdussamad (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to determine the influence of information technology-based career competencies and management on the work effectiveness of lecturers at Gorontalo State University. The approach in this study is quantitative. The research method is expost facto and correlational research design. The sample in the study was 92 people. The data analysis technique used is SEM-PLS. The results of the study showed that the SEM-PLS equation for community satisfaction was Ŷ = α + 0.681X + 0.231Z + ε with a determination coefficient of 71.80% and for service quality, namely Z = α + 0.642X + ε with a determination coefficient of 41.30%. The results of the hypothesis testing are (1) the competence of lecturers has a positive and significant effect on information technology-based career management at Gorontalo State University. (2) lecturer competence has a positive and significant effect on the effectiveness of lecturers' work in the implementation of the Tridharma of Higher Education at Gorontalo State University. (3) information technology-based career management has a positive and significant effect on the effectiveness of lecturers' work in the implementation of the Tridharma of Higher Education at Gorontalo State University. (4) lecturer competence through information technology-based career management has a positive and significant effect on the effectiveness of lecturers' work in the implementation of the Tridharma of Higher Education at Gorontalo State University. So that information technology-based career management is able to become a good intervening variable which means that information technology-based career management becomes a strategic bridge that strengthens the impact of competence on the achievement of tridharma performance.